ANALISIS URGENSI IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY - Rissa Marina Widodo (Ekonomi Syariah IAIN Kudus, 2014)
Tulisan ini menganalisi tentang implementasi Corporate Social Responsibility di perusahaan sebagai bentuk keikutsertaan perusahaan dalam program pembangunan ekonomi. Untuk menstimulasi perkembangan CSR dalam perkembangan ekonomi yang berkelanjutan, diperlukan model penerapan CSR yang efektif, sumber daya manusia dan perusahaan yang berkompeten, peraturan yang tepat dan etika bisnis serta dukungan dari masyarakat untuk menjaga agar penerapan CSR sesuai dengan tujuan yang diharapkan dan nilai-nilai sosial. Keberlanjutan program CSR terbukti sebagai alternative program untuk memeprkuat masyarakat dan menyelesaikan permaslahan sosial. Sinergitas antara perusahaan, masyarakat dan pemerintah akan menentukan keberhasilan proram yang berkelanjutan.Kata Kunci: CSR , Perusahaan, Pembangunan BerkelanjutanANALYSIS OF THE URGENCY OF CORPORATE SOSIAL RESPONSIBILITY. This article analyzes about the implementation of Corporate Social Responsibility (CSR) as a commitment of company or business to contribute in the sustainability economic development program. To stimulate the growth of CSR capably throw in to the sustainability of economic development, it is essential to have an effective CSR model, competent human resources and institutions, proficient regulation and code of ethics in business, as well as support from public sector to assure the implementation of CSR in line with the goals and the society value. The sustainability of CSR program is deliberated to be an alternative for society empowerment to solve social problems and environments that more and more complicated in the last decades. The synergy of business, society, and government to constantly construct and develop a good quality society life and environment will determine the success of sustainable development program.Keywords: Corporate Social Responsibility, Company, Sustainable Development